Management of Pleural Infection - Sundaralingam, Anand (Pulm Ther, 2020)
Pleural infection is a millennia-spanning condition that has proved challenging to treat over many years. Fourteen percent of cases of pneumonia are reported to present with a pleural effusion on chest X-ray (CXR), which rises to 44% on ultrasound but many will resolve with prompt antibiotic therapy. To guide treatment, parapneumonic effusions have been separated into distinct categories according to their biochemical, microbiological and radiological characteristics. There is wide variation in causative organisms according to geographical location and healthcare setting. Positive cultures are only obtained in 56% of cases; therefore, empirical antibiotics should provide Gram-positive, Gram-negative and anaerobic cover whilst providing adequate pleural penetrance. With the advent of next-generation sequencing techniques, yields are expected to improve. Complicated parapneumonic effusions and empyema necessitate prompt tube thoracostomy. It is reported that 16–27% treated in this way will fail on this therapy and require some form of escalation. The now seminal Multi-centre Intrapleural Sepsis Trials (MIST) demonstrated the use of combination fibrinolysin and DNase as more effective in the treatment of empyema compared to either agent alone or placebo, and success rates of 90% are reported with this technique. The focus is now on dose adjustments according to the patient’s specific ‘fibrinolytic potential’, in order to deliver personalised therapy. Surgery has remained a cornerstone in the management of pleural infection and is certainly required in late-stage manifestations of the disease. However, its role in early-stage disease and optimal patient selection is being re-explored. A number of adjunct and exploratory therapies are also discussed in this review, including the use of local anaesthetic thoracoscopy, indwelling pleural catheters, intrapleural antibiotics, pleural irrigation and steroid therapy.